Effect of 12-Week Interventions Involving Nordic Walking Exercise and a Modified Diet on the Anthropometric Parameters and Blood Lipid Profiles in Overweight and Obese Ex-Coal Miners - Sadowska-Krępa, Ewa; Gdańska, Agnieszka; Rozpara, Michał; Pilch, Wanda; Přidalová, Miroslava; Bańkowski, Sebastian (Obesity facts, 2020)
BACKGROUND: Overweight and obesity after retirement are likely to be caused by unhealthy eating habits and the energy intake exceeding the energy expenditure. OBJECTIVES: This study was designed to assess the effects of two 12-week interventions involving, respectively, either regular physical activity or a modified lower-calorie diet on the anthropometric parameters and blood lipid profiles in overweight and obese retired miners with lipid disorders. DESIGN: The study participants (n = 30, aged 58.7 ± 4.1 years, body height 174.8 ± 7.3 cm, body weight 96.6 ± 13.9 kg) were randomly assigned to 2 intervention groups: the Nordic walking group (NW), which exercised with intensity from 60 to 70% of participants' maximal heart rates for 1 h 3 times a week, and the modified diet group (MD). Modification of the diet consisted of reducing the daily energy intake by 30%, increasing the dietary content of mono- and polyunsaturated fatty acids and dietary fiber, and reducing the proportion of saturated fatty acids. The variables assessed at baseline and after 6 and 12 weeks were: anthropometric parameters (body weight, fat mass content [FM], fat percentage [BF], BMI, waist circumference [WC], hip circumference [HC], and waist-to-hip ratio [WHR]) and blood lipid indicators (total cholesterol [TC], triglycerides [TG], low density lipoprotein cholesterol [LDL-C], and high density lip-oprotein cholesterol [HDL-C]). RESULTS: The body weight of the participants in the NW was lower at week 12 by an average of 5 kg, BMI by 6%, FB by 19%, FM by 15%, WC by 8%, HC by 6%, and WHR by 3%. In the MD, the respective decreases were 8 kg and 8, 25, 20, 6, 2, and 7%. In the MD, the postintervention concentrations of TC and TG were within the reference range. CONCLUSION: Both 12-week interventions improved the anthropometric parameters and blood lipid profiles of retired heavy manual workers, with the improvements being more pronounced in the dieting group.
Keywords: obezita; tělesné váhy a míry; Triglycerides; Humans; Coal Mining; redukční dieta; index tělesné hmotnosti; lidé středního věku; Body Mass Index; Overweight; Retirement; Weight Reduction Programs; Diet, Reducing; Female; Aged; Polsko; Waist Circumference; lipidy; senioři; lidé; Poland; Waist-Hip Ratio; Lipid disorders; chůze; důchod; triglyceridy; ženské pohlaví; Male; Middle Aged; Physical activity; obvod pasu; Lipids; Walking; poměr pasu a boků; Obesity; Body Weight; Caloric restriction; tělesná hmotnost; mužské pohlaví; Body Weights and Measures; programy na snížení hmotnosti; nadváha; těžba uhlí